THE ROLE OF THE NOTARY SUPERVISORY COUNCIL IN ADDRESSING CIVIL LAW VIOLATIONS COMMITTED BY NOTARIES - Lukita, Hans; Gunadi, Ariawan (Awang Long Law Review, 2025)
The notary profession holds a strategic position in Indonesia’s civil law system due to its authority to produce authentic deeds with full evidentiary value. However, in practice, there are several cases in which notaries have been reported for alleged civil law violations, including drafting deeds that harm certain parties. This situation highlights the need for proportional legal protection and supervision of notaries as public officials. This study aims to analyze the supervisory mechanisms and the preventive role of the Notary Supervisory Council over notaries reported for civil law violations. This research uses a normative juridical method through literature review and case-based analysis. The findings show that notaries can still be held legally accountable if they are negligent or violate procedures in preparing deeds. In some instances, notarial deeds may be downgraded to private deeds or annulled by law. The Notary Supervisory Council plays a role in administering guidance and tiered supervision, including issuing administrative sanctions such as warnings or dismissals. Additionally, the Council serves as legal support to prevent criminalization of notaries who perform their duties professionally. In conclusion, notary supervision must be carried out fairly and proportionally while upholding the integrity of the profession; it is recommended that the Council’s preventive role be strengthened, particularly through legal assistance in civil cases.